(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Social responsibility of mass media – concept to which probably to put wide enough range of treatments. It is obvious that social responsibility specifies in correlation between various subjects of social and communicative interaction in which frameworks the journalist is responsible not only before those who supervises mass media, but first of all before a society.